Guillain-Barré Syndrome with Fatal Outcome during HIV-1-Seroconversion: A Case Report - Emanuele Pontali; Marcello Feasi; Maria Paola Crisalli; Giovanni Cassola (Case Reports in Infectious Diseases)
Guillain-Barré syndrome (GBS) is an acute or subacute peripheral polyneuropathy characterized by symmetrical muscle weakness. Its occurrence has been reported during acute HIV seroconversion since 1985. Among HIV-infected subjects, GBS has generally a favourable outcome. We report a case of GBS with fatal outcome during HIV seroconversion.